The Effectiveness of Game-Based Arabic Language Learning Using Biṭāqatu Al-Mufradāt on Student Learning Outcomes - Arrafi Hadisukma Irhamna; Roojil Fadillah (Fakultas Keguruan dan Ilmu Pendidikan - Universitas Gresik, 2026)
Arabic language instruction in pesantren-based schools still faces serious challenges, as most teachers rely on one-way lecture methods that cause students to become passive, easily bored, and unmotivated. This study aims to examine the effectiveness of game-based Arabic language learning using the Biṭāqatu al-Mufradāt medium compared to the lecture method on student learning outcomes, as well as to measure the magnitude of improvement through N-Gain analysis. This study employed a quantitative approach using a quasi-experimental design (Nonequivalent Control Group Design). A total of 50 tenth-grade students at SMA Daarut Tauhiid Boarding School in Bandung were divided into two groups: 25 students in the experimental group who learned through games, and 25 students in the control group who learned through lectures. Both groups took a pretest and a posttest, and the results were analysed using a paired samples t-test, an independent samples t-test, and N-Gain analysis with IBM SPSS version 25. The results showed that the average posttest score of the experimental group reached 82.68, far above that of the control group at 71.96 — a difference of 10.72 points. The independent samples t-test confirmed that this difference was statistically significant (t = −9.994; p < 0.001). The N-Gain analysis also showed that the improvement in the experimental group (mean N-Gain = 0.68, Moderate to High category) was greater than that of the control group (mean N-Gain = 0.41, Moderate category). Thus, Biṭāqatu al-Mufradāt has proven to be more effective in improving students' mastery of Arabic vocabulary and is worth considering as an alternative learning method in pesantren-based school settings.